Neoadjuvant Treatment Is Not Associated with Better Survival in T4 Non-Small Cell Lung Cancer - Özçıbık Işık, Gizem; Sarbay, İsmail; Bulut, Halil İbrahim; Kılıç, Burcu; Erşen, Ezel; Kara, H. Volkan; Kaynak, M. Kamil; Turna, Akif (Cerrahpaşa Medical Journal, 2024)
Objective: The best treatment strategy for T4 non-small cell lung cancer (NSCLC) has yet to be defined. However, studies have shown that surgical resection benefits selected patients without N2/N3 disease. We aimed to determine the effect of neoadjuvant chemotherapy and/or radiation therapy on survival in patients with T4N0-1 NSCLC. Methods: Between January 2002 and December 2020, 107 T4 patients who were operated on for NSCLC in our clinic were analyzed. Nine patients (8.3%) with T4N2 disease were excluded. Eighty-six patients (87.8%) received neoadjuvant high-dose radiation therapy and/or chemotherapy before resection. Twelve (12.2%) patients underwent surgical resection without induction chemotherapy or radiotherapy. Demographic characteristics, laboratory values, respiratory parameters, and pathological characteristics were recorded. Survival of the neoadjuvant+surgery and upfront surgery groups was calculated using the Kaplan–Meier test, while they were analyzed using both the log-rank test and Cox proportional-risk models. Results: In the neoadjuvant and upfront surgery groups, 10-year survival rates were 58.3% and 45.0%, respectively (hazard ratio: 1.39; 95% CI: 0.519-3.302; P = .567). Median survival times were 58, respectively. After adjustment for potential confounding variables, no statistically significant difference was found between the 2 groups in terms of survival (hazard ratio: 1.26; 95% CI: 0.49-3.21, P = .631) compared with the surgery-alone group. In addition, N1 disease was not found to be an independent prognostic factor (hazard ratio: 1.26; 95% CI: 0.49-3.21, P = .631). Conclusion: Aggressive treatment of T4N0 NSCLC with neoadjuvant chemotherapy and/or radiotherapy did not seem to prolong survival. Additionally, we did not find N1 to be a significant prognosticator. A prospective multicenter trial should evaluate these results. Cite this article as: Özçıbık Işık G, Sarbay İ, Bulut Hİ, et al. Neoadjuvant treatment is not associated with better survival in T4 nonsmall cell lung cancer. Cerrahpaşa Med J. 2024;48(3):238-242.